Measurement of the mass of the D0 meson - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We report a measurement of the D0 meson mass using the decay chain D∗(2010)+→D0π+ with D0→K−K−K+π+. The data were recorded with the BABAR detector at center-of-mass energies at and near the Υ(4S) resonance, and correspond to an integrated luminosity of approximately 477 fb−1. We obtain m(D0)=(1864.841±0.048±0.063) MeV, where the quoted errors are statistical and systematic, respectively. The uncertainty of this measurement is half that of the best previous measurement.